Peripheral Hole Acceptor Moieties on an Organic Dye Improve Dye‐Sensitized Solar Cell Performance. Issue 11 (1st September 2015) - Hao, Yan; Gabrielsson, Erik; Lohse, Peter William; Yang, Wenxing; Johansson, Erik M. J.; Hagfeldt, Anders; Sun, Licheng; Boschloo, Gerrit
Abstract : Investigation of charge transfer dynamics in dye‐sensitized solar cells is of fundamental interest and the control of these dynamics is a key factor for developing more efficient solar cell devices. One possibility for attenuating losses through recombination between injected electrons and oxidized dye molecules is to move the positive charge further away from the metal oxide surface. For this purpose, a metal‐free dye named E6 is developed, in which the chromophore core is tethered to two external triphenylamine (TPA) units. After photoinduced electron injection into TiO2, the remaining hole is rapidly transferred to a peripheral TPA unit. Electron–hole recombination is slowed down by 30% compared to a reference dye without peripheral TPA units. Furthermore, it is found that the added TPA moieties improve the electron blocking effect of the dye, retarding recombination of electrons from TiO2 to the cobalt‐based electrolyte. Abstract : A molecular sensitizer design, in which a chromophore is linked to peripheral hole acceptors, leads to more favorable electron transfer dynamics and improved dye‐sensitized solar cell performance. After photoinduced electron injection into TiO2, the remaining hole is rapidly transferred to a peripheral acceptor unit. These units also retard the recombination of electrons from TiO2 with the cobalt‐based electrolyte.